Parliament, Parties, Polls and Islam: Issues in the Current Debate on Religion and Politics in Pakistan - Babar Zaheer; Ali Bukhtiar; Hafiz Abdul Rehman Saleem; Haseeb Ahmad (Indus Journal of Social Sciences, 2025)
The relationship between religion and politics has played a critical role in Pakistan's political history, affecting everything from constitutional frameworks to the outcomes of elections. This study asks how religious political parties performed in the last parliamentary elections and how they affect the interaction between Islam and politics. It stresses the historical hurdles for Pakistan to reconcile Islamic precepts with democratic governance and the implications of these dynamics for the functioning of the legislature and the judiciary. Tehreek-e-Labbaik Pakistan (TLP) managed to win almost 4% of votes in the 2018 parliamentary election, most recently, among other religious parties. However, that influence does not always translate to significant National Assembly representation. This research explains the dynamics of success and decline experienced in the history of religious political entities and highlights the implications of their scope in the field of politics. The study also examines constitutional amendments and court verdicts, including a recent decision granting parliament the authority to appoint the Supreme Court’s chief justice, that have heightened debates over the balance of authority between political and religious bodies. These changes speak to the balancing act between democratic governance and Islamic State. The report offers suggestions to promote a more inclusive and balanced approach to religion and politics in Pakistan. Striving for democratic reforms, interfaith dialogue, and civic education, it hopes to enter into a political environment respectful of both Islamic tradition and democratic values. This research thus aspires to achieve a synergistic model of governance by developing a roadmap that would help address these challenges and facilitate a balanced and stable political environment with enough room for differences without compromising the stability of the religious and democratic institutions.